2022
DOI: 10.1016/j.vaccine.2022.01.055
|View full text |Cite
|
Sign up to set email alerts
|

Immunity debt or vaccination crisis? A multi-method evidence on vaccine acceptance and media framing for emerging COVID-19 variants

Abstract: Renewed COVID-19 outbreaks, stemming from the highly infectious Delta and Omicron variants, prompted rising fears of a ‘pandemic among the unvaccinated’. To address this prevalent vaccination crisis, media framing communication strategies can amplify the scientific evidence on COVID-19 vaccines to reach diverse geographic and socio-economic communities. The critical role of media framing strategies to engage and encourage large populations regarding vaccine acceptance has been rarely studied, despite growing e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 32 publications
2
18
0
Order By: Relevance
“…However, it is worth emphasizing that increasing vaccination coverage was the most important contributing factor in reducing hospitalizations and deaths. 21 , 22 Therefore, more effort should be invested in promoting the COVID-19 vaccine among the population.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is worth emphasizing that increasing vaccination coverage was the most important contributing factor in reducing hospitalizations and deaths. 21 , 22 Therefore, more effort should be invested in promoting the COVID-19 vaccine among the population.…”
Section: Discussionmentioning
confidence: 99%
“…During this time of new viral crisis, the topics of vaccination and immunity have also received intensified prominence in public forums. Once COVID vaccines were developed and approved, their relative merits and side-effects were publicly debated [3] , [4] , [5] . Google searches for the term ‘immunity’ and for COVID vaccines dramatically increased after the onset of the pandemic [6] , [7] .…”
Section: Introductionmentioning
confidence: 99%
“…Similar to public communication related to previous outbreaks of infectious diseases [6] or to the problem of antimicrobial resistance [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , messages about the importance of protecting others by engaging in hygienic practices or accepting recommended vaccination doses have also dominated news reports, government authorities’ announcements and public health campaigns [46] , [1] , [2] , [3] , [4] , [5] , [6] . People with COVID have been instructed to stay at home or in quarantine facilities, while others have been encouraged to physically distance from each other, wash their hands regularly, wear masks, accept vaccinations, seek testing if exposed or experiencing symptoms, and care for themselves at home if they do become ill with COVID [1] , [2] , [3] , [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] ...…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The communication-related factors have been reported as an effective tool in social and cause-related marketing (Jin et al, 2021 ). Several other studies underlined the role of communication messages in formulating people's actions (Yousaf et al, 2022 ). The efficacy of such communication campaigns (Jiang et al, 2021 ; Jin et al, 2021 ) and communication channels (Chen et al, 2022 ) are also reported in sectors of technology adoption.…”
Section: Communication Campaignsmentioning
confidence: 99%